Investigating biomechanical differences in lumbosacral transitional vertebrae among different Castellvi classifications - Weng, Rui; Yu, Yaoshuai; Ren, Ruxia; Chen, Yibin; Chen, Cairui; Xie, Siyuan; Li, Yikai; Zhang, Shaoqun (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveTo investigate the biomechanical differences among different Castellvi classifications of lumbosacral transitional vertebrae (LSTV) based on finite element analysis.MethodsUsing CT data of a healthy Asian adult male, a finite element model of the normal lumbar-pelvic complex and seven LSTV models (Castellvi types IA, IB, IIA, IIB, IIIA, IIIB, IV) were established. With bilateral acetabula fixed, 400 N axial compression (simulating body weight) and 8.0 Nm torque (simulating flexion, extension, lateral bending, rotation) were applied to each model. Differences in global displacement, maximum Mises stress of intervertebral discs and sacroiliac joints among the models were compared.ResultsIn terms of overall displacement, Types IIIA, IIIB, and IV were significantly lower than the normal model under all loading conditions; Types IA, IB, IIA, and IIB showed a significant reduction only under partial conditions (e.g., lateral bending, rotation). For the maximum Mises stress of intervertebral discs, Types IIIB and IV exhibited a significant reduction under all conditions; Type IIIA showed a significant reduction under all conditions except pure compression; Types IB and IIB had a significant reduction only under compression, extension, and lateral bending; Types IA and IIA showed increased stress under partial conditions (e.g., flexion, rotation). Regarding the maximum Mises stress of sacroiliac joints: the bilateral sacroiliac joints of Types IIIB and IV showed increased stress under all conditions except extension; the left sacroiliac joint of Type IIIA mainly showed an increase under most conditions, while the right side mainly showed a decrease; the bilateral sacroiliac joints of Types IB and IIB exhibited stress reduction under all conditions.ConclusionDifferent Castellvi classifications of LSTV exert significant biomechanical effects on the lumbar-pelvis complex. Among them, the IIIB and IV types (including the fused left side of the IIIA type) significantly increase sacroiliac joint stress, which may contribute to sacroiliac joint dysfunction or sacroiliac joint subluxation or sacroiliitis. Types IA and IIA may easily lead to discogenic low back pain due to increased local intervertebral disc stress and uneven stress distribution. Types ⅠB and ⅡB induce minimal interference in global displacement, intervertebral disc stress, and sacroiliac joint stress, resulting in a relatively lower risk of low back pain. These results provide a biomechanical reference for the classification-based diagnosis and intervention of LSTV-related low back pain.